Regulation of Renewable Resources in Federal Systems: The Case of Fishery in th EU - Frank Jensen; Niels Vestergaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 1999)
The EU regulation of fisheries is decided in two levels. The level of the total allowable catch (TAC) for the most important species is decided every year by the Council of Minsters. The TACs are allocated to the Member States as quotas. The Member States determine who is going to harvest the quota. There is, however, an information problem associated with this structure. It does not take into account how efficient fishermen in different countries are. In this paper we model the information problem as an adverse selection problem and analyse an EU tax coupled to effort as an alternative to the TAC system. We work with the hypothesis that EU suffers from a fiscal illusion and includes tax revenue in the objective function in order to finance other, also inefficient, operations. Even in the light of these imperfections there are at least two reasons for recommending an EU tax. First, it can be used to correct part of the market failure associated with fishery. Second, it can be used to secure correct revealation of types in the light of asymmetric information.
Keywords: 330